PERFORMA USAHA KEMITRAAN AYAM RAS PEDAGING - Cokorda Bagus Dharma Putra Mahardika; Wely Yitro Pello; Marchy Pallo (Partner, 2020)
The partnership scheme is a kind of cooperation between business with the farmers in term of livestock business management. The partner farmer groups act as plasma, while the partner of companies act as core. In the broiler partnership, the partner or core companies provide farming production facilities such as DOC, feed, medicines, technical supervising and product marketing, while the plasma provide the chicken house and worker. The research was conducted to evaluate the performance of broiler chicken farmer an income with partnership system. Total respondents were 122 farmers who joined to broiler contract farming. This sampling was conducted using by proportionate stratified random sampling. The results of the research showed that the depletion, body weight, FCR and PI was significantly affected on income but harvesting day isn’t significant. The lower the depletion, FCR or the higher body weight and PI, made higher the income level.